Approximation of functions belonging to LIP (α, p) class by (E, 1)(N,pn) means of its fourier series - Dhakal, Binod Prasad (Kathmandu University Journal of Science, Engineering and Technology, 2011)
The present paper deals with approximation of a function belonging to the Lip (α, p) class by product summability method. Here product of Euler (E,1) summability method and Nörlund (N, pn) method has been taken. A new estimate on degree of approximation of a function f belonging to Lip (α, p) class has been determined by (E,1) (N, pn) summability of a Fourier series. Subject Classification: 40G05, 42B05, 42B08 Keywords and phrases: Degree of approximation; (E,1)(N, pn) summability; Fourier series; Lip (α, p) class; Lp norm. DOI: http://dx.doi.org/ 10.3126/kuset.v7i1.5416 KUSET 2011; 7(1): 1-8